Feasibility Study of Shallot Production in Financial Aspect in Central Lampung (Case study : Kota Gajah) - Dian Fajarika; Rizqa Ula Fahadha; Intan Mardiono; Nur Miswari (Journal of Science and Applicative Technology, 2019)
Shallot is superior vegetable commodity in which the demand has a tendency to increase. The growth of demand for commodity is in line with the growth of population in Indonesia. Shallot is included in 7 (seven) basic foodstuffs targeted by Ministry of Agriculture in Indonesia. The need of shallot is supplied by Central Java, East Java, West Java and West Nusa Tenggara. Shallot commodities in Indonesia heavily depend on the season, the government makes a regulation about shallot import for maintaining stability of price. To anticipate the occurrence of imports, the government is focused on inviting local governments to create a farming center of shallot. Lampung Province is one of the provinces that has suitable natural resources for shallot farming. The purpose of this research is to analyze the financial feasibility of shallot farming development based on NPV (Net Present Value), Net B/C (benefit/cost), IRR (Internal Rate Return), and payback period criteria. The financial feasibility analysis through the calculation of cost and benefit components obtained from shallot business and investment criteria to determine the level of feasibility in quantitative terms. The result showed that NPV is IDR. 16,747,507.38, Net B/C 1.45, IRR for 4 period is 66.03% and payback period is 3.58.